2018
DOI: 10.1186/s12964-018-0235-0
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps induce aggregation of washed human platelets independently of extracellular DNA and histones

Abstract: BackgroundThe release of neutrophil extracellular traps (NETs), a mesh of DNA, histones and neutrophil proteases from neutrophils, was first demonstrated as a host defence against pathogens. Recently it became clear that NETs are also released in pathological conditions. NETs released in the blood can activate thrombosis and initiate a cascade of platelet responses. However, it is not well understood if these responses are mediated through direct or indirect interactions. We investigated whether cell-free NETs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 59 publications
4
93
1
4
Order By: Relevance
“…6,20 MPO activity is an index of neutrophil, monocyte/macrophage activation, whereas S100A8/ A9, which is abundantly stored in neutrophil cytoplasm, is another classical marker for neutrophil activation. 21,22 Therefore, we assayed both MPO and S100A8/A9 levels to assess activation of innate immune cells particularly neutrophils, in the sera of patients undergoing liver transplantation using commercially available kits.…”
Section: Measurement Of Mpo S100a8/9 and Multiple Cytokinesmentioning
confidence: 99%
“…6,20 MPO activity is an index of neutrophil, monocyte/macrophage activation, whereas S100A8/ A9, which is abundantly stored in neutrophil cytoplasm, is another classical marker for neutrophil activation. 21,22 Therefore, we assayed both MPO and S100A8/A9 levels to assess activation of innate immune cells particularly neutrophils, in the sera of patients undergoing liver transplantation using commercially available kits.…”
Section: Measurement Of Mpo S100a8/9 and Multiple Cytokinesmentioning
confidence: 99%
“…NETs represent part of a continuum of sterile inflammation and thrombosis that can involve all vascular beds, including the microvascular circulation [55][56][57][58][59][60][61][62][63][64][65][66].…”
Section: Nets and Microvascular Thrombosismentioning
confidence: 99%
“…Finally, the recent XANTHIPPE study demonstrated a reduction in PLAs in the ticagrelor group compared to placebo [113]. To date, no study reported a significant modulation of NETosis by P2Y 12 inhibitors, although ticagrelor was recently shown to reduce in vitro NET-induced platelet aggregation, secretion and expression of P-selectin [113,121].…”
Section: Platelet-leukocyte Interactions and Formation Of Neutrophilmentioning
confidence: 98%
“…NETs are large, web-like extracellular chromatin structures that are released by neutrophils upon various activating stimuli, including exogenous microorganisms (bacteria, fungi, virus, and parasites), immune complexes and activated platelets [120]. NETs can trap, neutralize and kill microorganisms, but also activate platelets and promote coagulation [121]. They are considered as critical players in many inflammatory conditions, especially sepsis-induced organ injuries, autoimmunity, tumorigenesis and metastasis [120].…”
Section: Platelet-leukocyte Interactions and Formation Of Neutrophilmentioning
confidence: 99%